(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2021)
This study investigates the information literacy skill on the use of library information resources among undergraduate students in Adamawa State. The objectives of the study are to find out the level of information literacy skill of undergraduate student in Adamawa state, to determine the level of use of the information resources and to determine the challenges faced in the use of these information resources. Quantitative method of data collection was used using survey research design. The study revealed that most of the student has high level of information literary skill and they use information resource for academic purposes to a high extent, it was revealed from the findings that inadequate current reading and research materials are the major problem facing the use of information resources in University libraries in Adamawa.